Exploring Inclusion in Secondary Schools: A Study on Dhaka City - Chaitee, Nazmun Nahar; Mallick, Biplob; Arefin, Md. Shamsul; Popy, Fatema Begum (Universitas Malikussaleh, 2020)
This paper presents findings of a mixed methods research which is mainly exploratory research by nature. The primary data have been collected from 180 students and 60 teachers by questionnaires, classroom observation and FGD. To analysis the data a descriptive triangulation approach is used. The Major purpose of this study is to present the practice of inclusive education on inclusive schooling in Dhaka city and other vulnerability discourses that elevated utmost challenges for survival of students with Disabilities (PWDs), disadvantage, gender discrimination during study time. The study findings explore multiple factors poses a threat to inclusion, as Bangladesh is considered one of the most growing concern countries in the world about inclusion. The study reveals that there is gender equity and empty gender discrimination in Dhaka city but still there is unpleasant proportion between student and teacher ratio. Although the lack of enough facilities, schools are welcoming different categories of students in their classroom while teachers are not always prepared to support students for ensuring quality education together with special need child. Though the different initiatives have been taken to train the teachers, which is a must for achieving goals but there is a lack of trained teachers in school to nurture the special need children whereas unified curriculum has been used with ICT teaching-learning materials. Making creative question is one of the most highly encouraging reforms in our country and whenever students take it positively but teachers either have a little idea or dislike the process. In this circumstances it is expected that the findings would influence policies for ensuring inclusive intervention of preparedness and rehabilitation.